Development of high performance supercapacitor using manganese oxide, conducting polymers and carbon-based fiber composites - Mohd Abdah, Muhammad Amirul Aizat (2019)
An efficient energy storage device, supercapacitors have received great attention in achieving high specific capacitance due to its unique characteristics such as rapid charging/discharging rate, high specific power and good long-term cyclability. The fabrication of hybrid supercapacitors has been exploited to enhance the electrocapacitive performance of the electrode. In the present work, manganese oxide (MnO2), conducting polymers and carbon based fiber composites were rationally designed and fabricated as symmetrical (polyvinyl alcohol (PVA)-graphene oxide (GO)-MnO2/poly (3,4-ethylenedioxythiophene) (PEDOT) (PVA-GO-MnO2/PEDOT), carbon nanofibers (CNFs)-MnO2/polypyrrole (PPy) (CNFs-MnO2/PPy) and functionalised carbon nanofibers (f-CNFs)/PPy/MnO2) and asymmetrical (f-CNFs/PEDOT/MnO2//activated carbon (AC) and porous functionalised carbon nanofibers (P-f-CNFs)/PEDOT/MnO2//PCNFs) (ASC) supercapacitors. The morphology and chemical properties of all prepared electrodes were examined by means of field emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR), Raman spectroscopy and X-ray diffraction (XRD). The MnO2 valence state (Mn4+) was confirmed by the presence of two distinctive peaks of MnO2 by X-ray photoelectron microscopy (XPS). Porous functionalised carbon nanofibers (P-f-CNFs) was initially optimised using different polyacrylonitrile /polytetrafluoroethylene (PAN/PTFE) blend ratio (1:2, 2:1, 2:3 and 3:2) in order to obtain mesoporous structure. Using PAN/PTFE (2:3), the capacitance of P-f-CNFs displayed the highest (176.6 F/g) with a specific surface area of 281 m2/g. The electrochemical performances of MnO2 based fiber composites were studied using two-electrode configuration in 1 M KCl electrolyte. Interestingly, the assembled ASC P-f-CNFs/PEDOT/MnO2//PCNFs showed an excellent specific capacitance of 719.8 F/g compared to f-CNFs/PPy/MnO2 (409.88 F/g), f-CNFs/PEDOT/MnO2//AC (354 F/g), CNFs-MnO2/PPy (315.80 F/g) and PVA-GO-MnO2/PEDOT (144.66 F/g) at 25 mV/s. A good synergistic effect contributed by each material in P-f-CNFs/PEDOT/MnO2//PCNFs possessed remarkable specific energy of 60.5 Wh/kg and specific power of 555.3 W/kg at 0.6 A/g, indicating excellent electrochemical capacity. In addition, the enhancement of surface wettability and good mechanical strength of P-f-CNFs/PEDOT/MnO2//PCNFs ASC demonstrated better cycle life with 104.6% initial capacitance over 5000 cycles compared to other electrodes. Three assembled ASC devices could successful light up 25 red light emitting diodes (LEDs), implying the capability of this material to be used in the practical supercapacitor application. Therefore, P-f-CNFs/PEDOT/MnO2//PCNFs could be considered as a prospective candidate for high performance supercapacitor due to its remarkable supercapacitive performance.